Introduction (Itinera, 2023)
This monographic section of volume 25 of Itinera stems largely from the discussions that took place during the two study days I organised on 13th and 14th. May 2021 at the Stensen Institute in Florence, entitled Ricerche in corso. These were planned on the occasion of the Moral Philosophy Seminars, held at the University of Florence, with the collaboration of Professor Maddalena Mazzocut-Mis and Professor Bruno Accarino, who were foundamental importance for these event, and I would like to take this opportunity to thank them.With the aim of continuing and enriching the debate of both days, this section not only brings together some of the contributions presented by the speakers, but it also aims to further involve other authors in the field of teratology, an area of study, which can seem somewhat impenetrable.The original title of the seminar “The Anatomical Monster” (the subtitle of which reads: “Figures of Irregularity, Mechanisms of Exclusion and Biological Naturalism”) evidently referred to the theme of so-called “monstrous births”.The attempt was to make evident certain themes that run through the various contributions; starting from the definition of abnormal and pathological as deviations from the norm, we move on to delineate the field of unforeseen variations - anomalies, alterations, and abnormalities. We continue to the visual representation of monstrosity, its aesthetic form and its capacity to reveal exaggerated figures that break the monotony of “normality” by virtue of unexpected juxtapositions. This includes the monsters that populated Cabinets of Curiosities as much as circuses, later housed in the collections and on the anatomical tables of 18th- and 19th-century naturalists; the analysis of the present perception of the monster, aimed at its ambiguity, considered as a union of contrasting features that stand out against a horizon that leads back to otherness and difference. The result is a varied and polymorphous collection, within which the investigation of the prodigious, the marvellous and the monstrous loom transversally from every single essay.
Keywords: monster, irregularity, exclusion, abnormal